2021
DOI: 10.1038/s42003-021-02375-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade in triple negative breast cancer influenced by B cells through myeloid-derived suppressor cells

Abstract: Triple negative breast cancer holds a dismal clinical outcome and as such, patients routinely undergo aggressive, highly toxic treatment regimens. Clinical trials for TNBC employing immune checkpoint blockade in combination with chemotherapy show modest prognostic benefit, but the percentage of patients that respond to treatment is low, and patients often succumb to relapsed disease. Here, we show that a combination immunotherapy platform utilizing low dose chemotherapy (FEC) combined with oncolytic virotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 89 publications
(4 reference statements)
2
11
0
Order By: Relevance
“…While neither therapy showed as much of an effect on tumor growth as the monotherapy approach did, the mice treated with the dual combination of FEC + oHSV-1 had delayed tumor progression and 10–20% durable responses to treatment ( Figure 1 ). These data are consistent with our previously published findings using this therapeutic combination [ 12 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…While neither therapy showed as much of an effect on tumor growth as the monotherapy approach did, the mice treated with the dual combination of FEC + oHSV-1 had delayed tumor progression and 10–20% durable responses to treatment ( Figure 1 ). These data are consistent with our previously published findings using this therapeutic combination [ 12 ].…”
Section: Resultssupporting
confidence: 94%
“…Asper our previous publications, microarray analysis showed that FEC + oHSV-1 therapy increased the genes associated with the B cell receptor signaling pathways. Of the top 100 genes from the B cell signature gene list that we previously published [ 12 ], 64 overlapped with the current dataset ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations